The senses of democracy : perception, politics, and culture in Latin America - Masiello, Francine (William & Bettye Nowlin series in art, history, and culture of the Western Hemisphere., 2018)
In The Senses of Democracy, Francine R. Masiello traces a history of perceptions expressed in literature, the visual arts, politics, and history from the start of the nineteenth century to the present day. A wide transnational landscape frames the book along with an original and provocative thesis: when the discourse on democracy is altered--when nations fall into crisis or the increased weight of modernity tests minds and nerves--the representation of our sensing bodies plays a crucial role in explaining order and rebellion, cultural innovation, and social change. Taking a wide arc of materials--periodicals, memoirs, political proclamations, and travel logs, along with art installations and fiction--and focusing on the technologies that supplement and enhance human perception, Masiello looks at the evolution of what she calls "sense work" in cultural texts, mainly from Latin America, that wend from the heights of romantic thought to the startling innovations of modernism in the early twentieth century and then to times of posthuman experience when cyber bodies hurtle through globalized space and human senses are reproduced by machines. Tracing the shifting debates on perceptions, The Senses of Democracy offers a new paradigm with which to speak of Latin American cultural history and launches a field for the comparative study of bodies, experience, pleasure, and pain over the continental divide. In the end, sense work helps us to understand how culture finds its location